ANALISIS PENGARUH FINTECH LENDING TERHADAP PEREKONOMIAN INDONESIA - Ladi Wajuba Perdini Fisabilillah; Nurul Hanifa (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
This purpose of this study to analyze the effect of financial technology peer to peer lending on the Indonesian economy in the digital era. This study uses a quantitative approach with time series data in the form of monthly fintech lending statistical reports from 2018 until September 2020 an monthly SEKI ( Indonesia Economic and Financial Statistics) reports from 2018 to September 2020. The analysis technique uses regressions. The result showed that P2P lending financial technology had a significant positive effect on Indonesia’s economic growth and had effect of 68,18 percent on economic growth. The conclusion of this study is that peer to peer lending financial technology has a significant positive effect on economic growth. This show that the more rapid the growth peer to peer lending in Indonesia, the more positive the impact will be on the Indonesian economy.